Glycididazole sodium combined with radioiodine therapy for patients with differentiated thyroid carcinoma (DTC) - Wen, Qiang (Int J Clin Exp Med, 2015)
The aim of the present study was to evaluate efficacy and side effects of glycididazole sodium (CMNa) combined with radioiodine therapy for patients with DTC cervical metastases. 53 patients of DTC cervical lymph node metastasis were randomly divided into 2 groups, where 24 cases were treated with 4.44 GBq of (131)I alone, 29 cases were treated with 800 mg/m(2) of CMNa combined with 4.44 GBq of (131)I. Peripheral blood samples were collected before and after treatment to perform measurements of routine blood test, liver function, renal function, parathyroid hormone (PTH), lymphocyte micronucleus rates and chromosome mutation. The results showed that rates of complete response (CR) in CMNa combined with radioiodine group (65.5%) were significantly higher than that in radioiodine monotherapy group (37.5%). Furthermore, CMNa combined with adioiodine treatment significantly increased the percentage of thyroglobulin (Tg) reduction at 12 weeks after treatment (P<0.05). There is no significant difference in blood routine, liver function, renal function, PTH, lymphocyte micronucleus rates and chromosome mutation rates before and 12 weeks after treatment (P>0.05). These results indicate 4.44 GBq of (131)I treatment combined with 800 mg/m(2) of CMNa could significantly improve clinical efficacy of DTC patients without increasing side effects.